The Science Novum as Metaphor-Analysis of Philip Dick’s ‘do Androids Dream of Electric Sheep?’ - Kalvikkarasi, Dr. G (International Journal of English Literature and Social Sciences (IJELS), 2019)
Abstract: Science fiction is a tale of futurity which narrates the unique world of science and technology foregrounding the human element in the text. Philip Dick’s Do Androids Dream of Electric Sheep? (1963) is a science fiction on postwar nuclear communities on earth caught in the quagmire of techno andys. The study analyses how science and technology acts as a metaphor in the text for narrating the impact of technology on humanity. It utilizes the concept of Novum as a broad framework and takes into account the notions of SF theorists, Dark Suvino, Robert Scholes and Damien Boderick which serves us with appropriate approaches towards the text. The study analyses the alternate realities of our existence which dangles between human intelligence and artificial intelligence succinctly exemplified in the text. The novel raises the question of 'what makes us human' in the world of man-machine symbiosis.